Spinel ion diode and preparation method thereof
By using spinel as the positive electrode material and carbon material as the negative electrode material, combined with alkaline electrolyte, spinel ion diodes are constructed, which solves the shortcomings of existing ion diodes in terms of rateability and cyclic stability, realizes efficient energy storage and conversion, and reduces manufacturing costs.
Patent Information
- Application Number
- CN202411653454.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-04-25
AI Technical Summary
Existing ion diodes have poor performance in terms of rateability and cyclic stability and cannot meet practical requirements.
Spinel is used as the positive electrode material of the diode, combined with carbon material as the negative electrode material, and an alkaline electrolyte is used to construct an ion diode through the selective redox reaction between spinel and anion ions in the alkaline electrolyte.
It realizes efficient energy storage and conversion, has high rectification ratio and good electrochemical activity, reduces device manufacturing costs and improves service life.
Smart Images

Figure CN119889938A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of capacitors, and in particular relates to an ion diode and a preparation method thereof. Background Art
[0002] In recent years, brain-computer interface technology has developed rapidly. However, there is still a certain gap between the two-way communication between the human brain and the computer and the practical level. This is mainly because the human brain and the computer use two different signal transmission media, ions and electrons, respectively. This difference in information carriers makes the human brain and computer systems have completely different operating mechanisms, and also brings huge challenges to the deep integration and interaction of the two systems. Ion-electron coupling devices can realize the organic combination of ion transmission and electron transfer in the same circuit, thus providing a possible medium for information transmission between biological systems and electronic devices. However, to truly realize the information interaction between biological systems and electronic devices, it is also necessary to design and develop devices with logical operation functions to complete the transmission, processing and feedback of information.
[0003] In 2019, Stefan Kaskel's research group in Germany first proposed the concept of supercapacitor diodes. Capacitive ion diodes (CAPodes) are a new type of electrochemical functional device based on supercapacitors. They have a device structure similar to that of supercapacitors and the unidirectional conduction characteristics of semiconductor diodes. They are considered to be the most promising basic components for building ion-electron coupling circuits. They have broad application prospects in future technical fields such as in vivo diagnosis and treatment, human-computer interfaces, and neural network interactions. However, the research on ion diodes is still in its infancy. Due to some problems with electrode materials and electrolytes themselves, existing ion diodes still have problems such as low rectification ratio (~8) and low specific capacitance (<40F g -1 ), poor stability, poor biocompatibility and high manufacturing cost, which cannot meet the requirements of practical application. In fact, an in-depth analysis of the working principle of ion diodes reveals that the electrochemical behavior of its unidirectional energy storage originates from the selective storage of anions and cations by electrode materials. Therefore, the design and development of electrode materials with good ion screening effect is very critical and also extremely challenging.
[0004] Patent publication number CN 115631950A discloses a pseudocapacitor-based supercapacitor diode and a preparation method thereof, wherein the pseudocapacitor-based supercapacitor diode comprises a pseudocapacitor material positive electrode, a carbon material negative electrode and an aqueous alkaline electrolyte, wherein the pseudocapacitor material is a metal oxide that can realize a single ion surface redox reaction in an aqueous alkaline electrolyte, and the pseudocapacitor material is selected from at least one of cobalt tetroxide, zinc cobaltate, hydrated tungsten trioxide and vanadium pentoxide. The device successfully integrates the unidirectional conduction characteristics of the diode into the pseudocapacitor, thereby achieving the corresponding functions of unidirectional ion conduction / storage and effective blocking of unidirectional current. However, the electronic conductivity and structural stability of pseudocapacitor materials are poor, resulting in a small improvement in rate capability and cycle stability. Summary of the invention
[0005] In response to the technical problems of poor rate capability and cycle stability of ion diodes, the present invention proposes a spinel ion diode and a preparation method thereof. Based on the selective redox reaction between the spinel electrode and the anions and cations in the alkaline electrolyte, an ion diode is successfully constructed, which realizes energy storage in a single charging direction, greatly reduces the device manufacturing cost, and has greater practical application value.
[0006] In order to achieve the above object, the technical solution of the present invention is achieved as follows:
[0007] A spinel ion diode comprises a positive electrode, a carbon negative electrode and an alkaline electrolyte, wherein the active material in the positive electrode is spinel, and the spinel is any one of CoNi2S4, CuCo2S4 or NiCo2S4.
[0008] A method for preparing a spinel ion diode comprises the following steps:
[0009] S1, dispersing spinel, binder I and conductive additive I in solvent I, mixing to form positive electrode slurry, applying the obtained positive electrode slurry to a conductive current collector, and pressing to form a positive electrode sheet after drying;
[0010] S2, dispersing the carbon material, the binder II and the conductive additive II in the solvent II, mixing to form a negative electrode slurry, applying the obtained negative electrode slurry to the conductive current collector, and pressing the negative electrode sheet after drying;
[0011] S3. Assemble the positive electrode sheet, the separator, and the negative electrode sheet, add an alkaline electrolyte, and then package them to prepare a spinel ion diode.
[0012] The mass ratio of the spinel, the binder I and the conductive additive I is (7-8): (1-2): (1-2); the concentration of the spinel in the positive electrode slurry is 10-50 mg / ml.
[0013] The mass ratio of the carbon material, the binder II and the conductive additive II is (7-8): (1-2): (1-2); the concentration of the carbon material in the negative electrode slurry is 10-50 mg / ml.
[0014] The binder I and the binder II are independently selected from sodium carboxymethyl cellulose, polytetrafluoroethylene, and polyvinylidene fluoride.
[0015] The conductive additive I and the electrical additive II are independently selected from one of acetylene black, Ketjen black, conductive graphite, carbon nanotubes and graphene.
[0016] The solvent I and the solvent II are independently selected from one of glycerol, N-methylpyrrolidone, diethyl carbonate and ethanol.
[0017] The carbon material is one of activated carbon, graphite and hard carbon.
[0018] The electrolyte in the alkaline electrolyte is potassium hydroxide or sodium hydroxide.
[0019] The concentration of the alkaline electrolyte is 1-7 mol / L.
[0020] The conductive current collector is one of foam nickel, carbon paper, carbon fiber, carbon cloth, and stainless steel mesh.
[0021] The diaphragm is one of glass fiber, non-woven fabric, filter paper and ceramic membrane.
[0022] Preferably, in the spinel ion diode, the mass ratio of the spinel loaded on the positive electrode sheet to the carbon material loaded on the negative electrode sheet is 1:1-1:5.
[0023] Beneficial effects of the present invention: The present invention uses spinel nanomaterials as the positive electrode material of the diode, which has a higher theoretical energy density, which means that more energy can be stored, and a longer service life and higher energy output can be provided. In addition, good electrochemical activity helps the diode to achieve efficient energy conversion and has a good rectification ratio. The present invention uses environmentally friendly, low-cost aqueous electrolytes and common transition metal compounds to construct non-traditional spinel ion diodes. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0025] Figure 1The cyclic voltammetry curves of the spinel ion diode at different scan rates.
[0026] Figure 2 This is a comparison diagram of the area capacity of the prepared spinel ion diode in the positive bias and negative bias regions of the cyclic voltammetry curve at different scan rates.
[0027] Figure 3 This is the specific capacity diagram of the prepared spinel ion diode at different scanning speeds.
[0028] Figure 4 The curve of the rectification ratio I of the spinel ion diode prepared in the embodiment of the present invention versus the scanning rate.
[0029] Figure 5 This is a curve showing the change of rectification ratio II of the spinel ion diode prepared in an embodiment of the present invention with the scanning rate.
[0030] Figure 6 This is the constant voltage charging curve of the spinel ion diode at -0.6V and +1.0V, and the charging time is 3 seconds.
[0031] Figure 7 The constant voltage charging curve of the spinel ion diode at -0.6V and +1.0V, and the charging time is 5 seconds.
[0032] Figure 8 The constant voltage charging curve of the spinel ion diode at -0.6V and +1.0V, and the charging time is 10 seconds. DETAILED DESCRIPTION
[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] Example 1
[0035] A spinel ion diode, the preparation method comprising the following steps:
[0036] (1) Preparation of positive electrode sheet: Cobalt nickel sulfur (CoNi2S4), conductive graphite and vinylidene fluoride (concentration of 10 wt%) were dissolved in N-methylpyrrolidone (NMP) solvent at a mass ratio of 8:1:1, and then ground evenly in a mortar to obtain a stable and uniform slurry. The concentration of nickel, cobalt and sulfur in the slurry was 20 mg / ml, and the obtained mixed slurry was coated on a 1×1 cm 2The positive electrode sheet was prepared by drying in an oven at 80°C overnight and pressing at a pressure of 10 MPa. The loading amount of the positive electrode active material on the current collector was 2 mg / cm 2 ;
[0037] (2) Preparation of negative electrode sheet: Activated carbon, conductive graphite and vinylidene fluoride (concentration of 10 wt%) were dissolved in N-methylpyrrolidone (NMP) solvent at a mass ratio of 8:1:1, and then ground evenly in a mortar to obtain a stable and uniform slurry. The concentration of activated carbon in the slurry was 20 mg / ml, and the resulting mixed slurry was coated on a 1×1 cm 2 The negative electrode sheet was prepared by drying in an oven at 80°C overnight and pressing at a pressure of 10 MPa. The loading amount of activated carbon on the current collector was 3 mg / cm 2 ;
[0038] (3) Assemble the prepared positive and negative electrode sheets, place the positive electrode sheet into a 2032-type positive electrode shell, place the glass fiber separator and the negative electrode sheet in turn, inject 300 μL of 3 mol / L KOH electrolyte, then place the gasket and the negative electrode shell in turn, and finally package them to make a spinel ion diode.
[0039] Example 2
[0040] A spinel ion diode, the preparation method comprising the following steps:
[0041] (1) Preparation of positive electrode sheet: Nickel cobalt sulfur (NiCo2S4), carbon nanotubes and vinylidene fluoride (concentration of 10 wt%) were dissolved in ethanol solvent at a mass ratio of 8:1:1, and then ground evenly in a mortar to obtain a stable and uniform slurry. The concentration of nickel cobalt sulfur in the slurry was 20 mg / ml. The obtained mixed slurry was coated on a 1×1 cm 2 The positive electrode sheet was prepared by drying in an oven at 80°C overnight and pressing at a pressure of 10 MPa. The loading amount of the positive electrode active material on the current collector was 2 mg / cm 2 ;
[0042] (2) Preparation of negative electrode sheet: Activated carbon, carbon nanotubes and vinylidene fluoride (concentration of 10 wt%) were dissolved in ethanol solvent at a mass ratio of 8:1:1, and then ground evenly in a mortar to obtain a stable and uniform slurry. The concentration of activated carbon in the slurry was 20 mg / ml, and the obtained mixed slurry was coated on a 1×1 cm 2 After drying in an oven at 80°C overnight and pressing at a pressure of 10 MPa, the negative electrode sheet was obtained. The loading amount of activated carbon on the current collector was 6 mg / cm 2 ;
[0043] (3) Assemble the prepared positive and negative electrode sheets, place the positive electrode sheet into a 2032-type positive electrode shell, place the glass fiber separator and the negative electrode sheet in turn, inject 300 μL of 6 mol / L KOH electrolyte, then place the gasket and the negative electrode shell in turn, and finally package them to make a spinel ion diode.
[0044] Example 3
[0045] A spinel ion diode, the preparation method comprising the following steps:
[0046] (1) Preparation of positive electrode sheet: Nickel cobalt sulfur (NiCo2S4), acetylene black and vinylidene fluoride (concentration of 10 wt%) were dissolved in nitrogen methyl pyrrolidone solvent at a mass ratio of 8:1:1, and then ground evenly in a mortar to obtain a stable and uniform slurry. The concentration of nickel cobalt sulfur in the slurry was 20 mg / ml, and the obtained mixed slurry was coated on a 1×1 cm 2 The positive electrode sheet was prepared by drying in an oven at 80°C overnight and pressing at a pressure of 10 MPa. The loading amount of the positive electrode active material on the current collector was 2 mg / cm 2 ;
[0047] (2) Preparation of negative electrode sheet: Hard carbon, acetylene black and vinylidene fluoride (concentration of 10 wt%) were dissolved in nitrogen methyl pyrrolidone solvent in a mass ratio of 8:1:1, and then ground evenly in a mortar to obtain a stable and uniform slurry. The concentration of hard carbon in the slurry was 20 mg / ml, and the obtained mixed slurry was coated on a 1×1 cm 2 After drying in an oven at 80°C overnight and pressing at a pressure of 10 MPa, the negative electrode sheet was obtained. The loading amount of hard carbon on the current collector was 10 mg / cm 2 ;
[0048] (3) Assemble the prepared positive and negative electrode sheets, place the positive electrode sheet into a 2032-type positive electrode shell, place the glass fiber separator and the negative electrode sheet in turn, inject 300 μL of 6 mol / L NaOH electrolyte, then place the gasket and the negative electrode shell in turn, and finally package them to make a spinel ion diode.
[0049] Electrochemical cycle stability test
[0050] In order to test the storage performance of the prepared spinel ion diode, electrochemical performance tests were carried out using Shanghai Chenhua CHI660E.
[0051] The experimental results are as follows Figure 1-8 shown.
[0052] Figure 1The cyclic voltammetry curves of the button cell assembled with the sample of Example 1 at different scan rates in the -0.6-1V voltage window show that the shape of the curve remains basically unchanged even if the scan rate is increased to 100mV / s, indicating that the modified material has good rate capability.
[0053] Figure 2 The area capacity comparison of the cyclic voltammetry curve in the positive bias and negative bias regions at different scan rates for the button battery assembled by the sample of Example 1. It can be seen from the figure that at different scan rates, the capacity in the positive bias region is much larger than that in the negative bias region, which also indicates that the device has certain application value in the field of capacitor diodes.
[0054] Figure 3 This is a graph of the specific capacity of the sample in Example 2 at different scanning speeds. It can be seen from the graph that when the scanning speed increases from 5 to 100 mV / s, the corresponding specific capacity is 91.0, 54.8, 43.7, 38.9, 34.5, and 26.8 coulombs per gram.
[0055] Figure 4 This is the curve of the rectification ratio I changing with the scanning speed for the sample in Example 2 at different scanning speeds. It can be seen from the figure that as the scanning speed increases, the rectification ratio I also increases. When the scanning speed is 100mV / s, the rectification ratio I can reach 13.8.
[0056] Figure 5 This is the curve of the rectification ratio II changing with the scanning speed for the sample in Example 3. It can be seen from the figure that with the change of the scanning speed, the rectification ratio II also fluctuates between 0.7 and 0.8, maintaining this good rectification ratio.
[0057] Figure 6-8 This is a constant voltage charging curve diagram of the sample of Example 1 at -0.6V and +1.0V. It can be seen from the figure that when charging at a positive voltage of 1.0V, the current response decreases slowly, and when charging at -0.6V, the current has almost no response.
[0058] Example 4
[0059] A spinel ion diode, the preparation method comprising the following steps:
[0060] (1) Preparation of positive electrode sheet: Copper cobalt sulfur (CuCo2S4), acetylene black and polytetrafluoroethylene emulsion (concentration of 60wt%) were dissolved in nitrogen methyl pyrrolidone solvent in a mass ratio of 8:2:1, and then ground evenly in a mortar to obtain a stable and uniform slurry. The concentration of nickel cobalt sulfur in the slurry was 10mg / ml, and the obtained mixed slurry was coated on a 1×1cm 2 The positive electrode sheet was prepared after drying in an oven at 80°C overnight and pressing at a pressure of 10 MPa. The loading amount of the positive electrode active material on the current collector was 5 mg / cm2 ;
[0061] (2) Preparation of negative electrode sheet: Graphite, acetylene black and vinylidene fluoride (concentration of 10 wt%) were dissolved in nitrogen methyl pyrrolidone solvent in a mass ratio of 8:1:1, and then ground evenly in a mortar to obtain a stable and uniform slurry. The concentration of hard carbon in the slurry was 30 mg / ml, and the obtained mixed slurry was coated on a 1×1 cm 2 The negative electrode sheet was prepared by drying in an oven at 80°C overnight and pressing at a pressure of 10 MPa. The loading amount of graphite on the current collector was 10 mg / cm 2 ;
[0062] (3) Assemble the prepared positive and negative electrode sheets, place the positive electrode sheet into a 2032-type positive electrode shell, place the glass fiber separator and the negative electrode sheet in turn, inject 300 μL of 6 mol / L NaOH electrolyte, then place the gasket and the negative electrode shell in turn, and finally package them to make a spinel ion diode.
[0063] Example 5
[0064] A spinel ion diode, the preparation method comprising the following steps:
[0065] (1) Preparation of positive electrode sheet: Nickel cobalt sulfur (NiCo2S4), acetylene black and polytetrafluoroethylene emulsion (concentration of 60wt%) were dissolved in diethyl carbonate solvent at a mass ratio of 7:1:2, and then ground evenly in a mortar to obtain a stable and uniform slurry. The concentration of nickel cobalt sulfur in the slurry was 50mg / ml, and the obtained mixed slurry was coated on a 1×1cm 2 The positive electrode sheet was prepared after drying in an oven at 80°C overnight and pressing at a pressure of 10 MPa. The loading amount of the positive electrode active material on the current collector was 5 mg / cm 2 ;
[0066] (2) Preparation of negative electrode sheet: Graphite, acetylene black and polytetrafluoroethylene emulsion (concentration of 60 wt%) were dissolved in nitrogen methyl pyrrolidone solvent in a mass ratio of 8:1:2, and then ground evenly in a mortar to obtain a stable and uniform slurry. The concentration of hard carbon in the slurry was 30 mg / ml, and the obtained mixed slurry was coated on a 1×1 cm 2 The negative electrode sheet was prepared by drying in an oven at 80°C overnight and pressing at a pressure of 10 MPa. The loading amount of graphite on the current collector was 10 mg / cm 2 ;
[0067] (3) Assemble the prepared positive and negative electrode sheets, place the positive electrode sheet into a 2032-type positive electrode shell, place the glass fiber separator and the negative electrode sheet in turn, inject 300 μL of 1 mol / L NaOH electrolyte, then place the gasket and the negative electrode shell in turn, and finally package them to make a spinel ion diode.
[0068] Example 6
[0069] A spinel ion diode, the preparation method comprising the following steps:
[0070] (1) Preparation of positive electrode sheet: Cobalt nickel sulfur (CoNi2S4), conductive graphite and vinylidene fluoride (concentration of 10 wt%) were dissolved in N-methylpyrrolidone (NMP) solvent at a mass ratio of 8:1:1, and then ground evenly in a mortar to obtain a stable and uniform slurry. The concentration of nickel, cobalt and sulfur in the slurry was 10 mg / ml, and the obtained mixed slurry was coated on a 1×1 cm 2 The positive electrode sheet was prepared by drying in an oven at 80°C overnight and pressing at a pressure of 10 MPa. The loading amount of the positive electrode active material on the current collector was 5 mg / cm 2 ;
[0071] (2) Preparation of negative electrode sheet: Activated carbon, conductive graphite and sodium carboxymethyl cellulose were dissolved in propylene glycol solvent in a mass ratio of 7:2:2, and then ground evenly in a mortar to obtain a stable and uniform slurry. The concentration of activated carbon in the slurry was 50 mg / ml, and the obtained mixed slurry was coated on a 1×1 cm 2 The negative electrode sheet was prepared by drying in an oven at 80°C overnight and pressing at a pressure of 10 MPa. The loading amount of activated carbon on the current collector was 5 mg / cm 2 ;
[0072] (3) Assemble the prepared positive and negative electrode sheets, place the positive electrode sheet into a 2032-type positive electrode shell, place the glass fiber separator and the negative electrode sheet in turn, inject 300 μL of 7 mol / L NaOH electrolyte, then place the gasket and the negative electrode shell in turn, and finally package them to make a spinel ion diode.
[0073] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A spinel ion diode, comprising a positive electrode, a carbon negative electrode and an alkaline electrolyte, characterized in that: The active material in the positive electrode is spinel, and the spinel is any one of CoNi2S4, CuCo2S4 or NiCo2S4.
2. The method for preparing the spinel ion diode according to claim 1, characterized in that: The following steps are involved: S1, dispersing spinel, binder I and conductive additive I in solvent I, mixing to form positive electrode slurry, applying the obtained positive electrode slurry to a conductive current collector, and pressing to form a positive electrode sheet after drying; S2, dispersing the carbon material, the binder II and the conductive additive II in the solvent II, mixing to form a negative electrode slurry, applying the obtained negative electrode slurry to the conductive current collector, and pressing the negative electrode sheet after drying; S3. Assemble the positive electrode sheet, the separator, and the negative electrode sheet, add an alkaline electrolyte, and then package them to prepare a spinel ion diode.
3. The method for preparing the spinel ion diode according to claim 2, characterized in that: The mass ratio of the spinel, the binder I and the conductive additive I is (7-8): (1-2): (1-2).
4. The method for preparing the spinel ion diode according to claim 2, characterized in that: The mass ratio of the carbon material, the binder II and the conductive additive II is (7-8): (1-2): (1-2).
5. The method for preparing the spinel ion diode according to claim 2, characterized in that: The binder I and the binder II are independently selected from sodium carboxymethyl cellulose, polytetrafluoroethylene, and polyvinylidene fluoride.
6. The method for preparing the spinel ion diode according to claim 2, characterized in that: The conductive additive I and the electrical additive II are independently selected from one of acetylene black, Ketjen black, conductive graphite, carbon nanotubes and graphene.
7. The method for preparing the spinel ion diode according to claim 2, characterized in that: The solvent I and the solvent II are independently selected from one of glycerol, N-methylpyrrolidone, diethyl carbonate or ethanol.
8. The method for preparing the spinel ion diode according to claim 2, characterized in that: The carbon material is one of activated carbon, graphite or hard carbon.
9. The method for preparing the spinel ion diode according to claim 2, characterized in that: The electrolyte in the alkaline electrolyte is potassium hydroxide or sodium hydroxide.
10. The method for preparing a spinel ion diode according to claim 9, characterized in that: The concentration of the alkaline electrolyte is 1-7 mol / L.
Citation Information
Patent Citations
Pseudocapacitor-based supercapacitor diode and preparation method thereof
CN115631950A